2018
DOI: 10.1016/j.archger.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health and its association with all-cause mortality of older adults in Poland: The PolSenior project

Abstract: SRH was associated with mortality in both genders. After adjustment for age, this relationship was maintained in respondents with poor compared to good SRH. Inclusion of potential confounders demonstrated that SRH was an independent predictor of mortality only in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 42 publications
6
33
0
Order By: Relevance
“…Our findings were similar to those of previous studies that reported a correlation between a poor SRH and a high hs-CRP level ( [7][8][9]22]. In a study of 4049 respondent older adults without significant cognitive deficit by Szybalska et al [23], a worse SRH was associated with increased interleukin-6 (IL-6) and CRP levels. Leshem-Rubinow et al [7] analyzed the correlations between SRH and the inflammation-sensitive biomarkers hs-CRP and fibrinogen in 13,773 healthy individuals and observed higher biomarker levels in the group with the lowest SRH level; hs-CRP showed a correlation in both males and females, but fibrinogen only showed a correlation in males.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings were similar to those of previous studies that reported a correlation between a poor SRH and a high hs-CRP level ( [7][8][9]22]. In a study of 4049 respondent older adults without significant cognitive deficit by Szybalska et al [23], a worse SRH was associated with increased interleukin-6 (IL-6) and CRP levels. Leshem-Rubinow et al [7] analyzed the correlations between SRH and the inflammation-sensitive biomarkers hs-CRP and fibrinogen in 13,773 healthy individuals and observed higher biomarker levels in the group with the lowest SRH level; hs-CRP showed a correlation in both males and females, but fibrinogen only showed a correlation in males.…”
Section: Discussionsupporting
confidence: 91%
“…Our ndings were similar to those of previous studies that reported a correlation between a poor SRH and a high hs-CRP level ( [7][8][9]26]. In a study of 4,049 respondent older adults without signi cant cognitive de cit by Szybalska et al [27], a worse SRH was associated with increased interleukin-6 (IL-6) and CRP levels. Leshem-Rubinow et al [7] analyzed the correlations between SRH and the in ammation-sensitive biomarkers hs-CRP and brinogen in 13,773 healthy individuals and observed higher biomarker levels in the group with the lowest SRH level; hs-CRP showed a correlation in both men and women, but brinogen only showed a correlation in men.…”
Section: Discussionsupporting
confidence: 91%
“…Among elderly people who reported a diagnosis of cancer, about 17% considered their health bad or very bad at the time of the research, with a higher frequency observed in those with a diagnosis time of less than 5 years (23.5% versus 11.4%), regardless of gender, age and the presence of other chronic diseases. Self-rated health is an indicator that integrates the individual's biological, psychological and social perception, reflecting the presence of functional limitations and quality of life, in addition to being considered a predictor of mortality 23,24 . Still, it is considered an important indicator of the impact of the disease on individual well-being 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Self-rated health is an indicator that integrates the individual's biological, psychological and social perception, reflecting the presence of functional limitations and quality of life, in addition to being considered a predictor of mortality 23,24 . Still, it is considered an important indicator of the impact of the disease on individual well-being 24 .…”
Section: Discussionmentioning
confidence: 99%